A Multi-dimensional Reputation System Combined with Trust and Incentive Mechanisms in P2P File Sharing Systems - Yang, Mao; Feng, Qinyuan; Dai, Yafei; Zhang, Zheng (IEEE Computer Society, 2007)
Free-riders and fake files are two important problems in P2P file sharing systems. Previous works have always used incentive mechanisms and trust mechanisms to ad dress them respectively. In real systems however, a trust mechanism without incentive would face lack of users' enthusiasm and thus cause sparse relationship of direct trust while an incentive mechanism without trust could induce users' bad behavior. A novel reputation system is proposed in this paper that combines trust and incentive mechanisms. It uses ¯les' vote and retention time, down load volume and users' rank to construct a more extensive direct trust relationship and calculates a user's reputa tion with a multi-trust algorithm. It can identify fake files and provide service differentiation with reputation. Im plementation and some security consideration in DHT are also discussed.